Preparing the Income and Health of Prospective Hajj and Umrah Pilgrims in Langsa City - Elfida, Elfida; Susanti, Susanti; Sulistiany, Eva; Junaida, Erni; Afnina, Afnina (CV. Rayyan Dwi Bharata, 2025)
The community service activities carried out in the hall of STIKes Bustanul Ulum Langsa aim to convince prospective pilgrims and the community in Langsa to change their mainset regarding their income capabilities so that they can immediately go to the holy land with favorable health conditions. So far they are afraid and feel worried about not being able to pay the fee according to the specified date and poor health conditions. Based on these problems, this community service activity needs to be carried out to convince and provide solutions for participants of the strength of their income and health so that they can immediately go to the holy land happily and comfortably in worship. The number of participants was 74 people consisting of prospective Hajj and Umrah pilgrims and the community who were invited guests. The methods used were lectures, discussions, and questions and answers. The results of this activity had a positive impact on participants because they became confident in their income capabilities and understood how to maintain their health in preparation for travel and worship.